Embolia paradoxal múltipla durante Colangiopancreatografia Retrógrada Endoscópica – Caso Clínico - Vaz, Inês; Moreira, Daniela; Oliveira, Carmen (Journal of the Portuguese Society of Anesthesiology, 2023)
A 73-year-old man diagnosed with common bile duct stones presented for endoscopic retrograde cholangiopancreatography (ERCP). The procedure was managed with sedation, during which a pulseless electrical cardiac arrest occurred with recovery after 5 minutes. During the assessment a second cardiorespiratory arrest followed. After cardiac defibrillation, echocardiography revealed air within the left heart chambers and severely depressed ventricular function. Patient’s neurological function was never restored, and cerebral CT scan revealed bilateral lesions with probable embolic source. Supporting the very poor prognosis described in the literature, the patient died 7 days after the procedure.